Exploring Language Preferences and Perceptions: A Comparative Study of English and Yoruba among Adolescents in Oyo State, Nigeria - Oyeyemi Jumoke Jekayinfa; Bello Yekeen; Surajudeen Adewale Badru; Aminat Ozohu Aburime (Universitas Pendidikan Ganesha, 2024)
It is astonishing that many senior school-aged adolescents in Oyo State do not grasp English or make grammatically acceptable responses, but freely express themselves in Yoruba. This study therefore comparatively analyse school-going adolescents’ attitudes to English and Yoruba Languages in Oyo State, Nigeria. This was a descriptive survey of research type. The population for this study comprised all school-going adolescents in Oyo State. Four hundred and seventy-one (471) school-going adolescents were sampled for this study using a multi-stage sampling technique. A researcher’s designed questionnaire with a reliability coefficient of 0.77 was used for data collection while the data collected were analysed using descriptive statistics of percentage to answer the research questions and inferential statistics of independent t-test and a two-way Analysis of Variance (2-way ANOVA) to test the hypotheses postulated at 0.05 alpha level. Findings from this study revealed that the most widely spoken language among secondary school students in Oyo State was English; the attitude of secondary school students to English and Yoruba Languages was positive. It was therefore recommended among others that school-going adolescents in school should maintain a positive attitude towards learning English without abandoning their home tongue, particularly Yoruba, to enhance their academic performance; English and Yoruba teachers can engage students by simplifying and sequentially teaching language to foster a positive attitude towards learning.